2021
DOI: 10.7759/cureus.19923
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Perceived Barriers to Treating Opioid Use Disorder in the Emergency Department

Abstract: We aimed to assess physicians' perceptions of barriers to starting medication-assisted treatment (MAT) in the Emergency Department (ED), views of the utility of MAT, and abilities to link patients with opioid use disorder (OUD) to MAT programs in their respective communities. MethodsThis was a cross-sectional survey study of American emergency medicine (EM) physicians with a selfadministered online survey via SurveyMonkey (Survey Monkey, San Mateo, California). The survey was emailed to the Council of Residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A US study showed that only 20.9% of emergency department physicians felt ready to prescribe buprenorphine–naloxone, citing a lack of formal training, limited knowledge of resources and absence of local protocols and referral networks. 17 Other research similarly suggests that barriers to OAT initiated in the emergency department include a shortage of trained prescribers and limited knowledge of outpatient follow-up options; 18 fewer than half of emergency department clinicians felt comfortable initiating methadone. 19 More research is needed to further elucidate the reasons for low OAT prescribing within hospital settings in Ontario, but effective responses may include providing institutional OAT training, establishing OAT initiation protocols in acute care settings, organizing and promoting awareness of referral networks with outpatient addictions programs, 20 and improving prescribing for patient-initiated discharges.…”
Section: Discussionmentioning
confidence: 99%
“…A US study showed that only 20.9% of emergency department physicians felt ready to prescribe buprenorphine–naloxone, citing a lack of formal training, limited knowledge of resources and absence of local protocols and referral networks. 17 Other research similarly suggests that barriers to OAT initiated in the emergency department include a shortage of trained prescribers and limited knowledge of outpatient follow-up options; 18 fewer than half of emergency department clinicians felt comfortable initiating methadone. 19 More research is needed to further elucidate the reasons for low OAT prescribing within hospital settings in Ontario, but effective responses may include providing institutional OAT training, establishing OAT initiation protocols in acute care settings, organizing and promoting awareness of referral networks with outpatient addictions programs, 20 and improving prescribing for patient-initiated discharges.…”
Section: Discussionmentioning
confidence: 99%
“… 87 In a Kentucky study, physicians without an X-Waiver were less likely to report positive personal beliefs about using medications to treat OUD compared to physicians who had an X-Waiver. 88 While the recommendation to include X-Waiver requirements as a part of residency training were proposed in the literature, 89 implementation remained limited.…”
Section: Legislative Response and Fda Approval Of Buprenorphinementioning
confidence: 99%
“…EM residents are more eager to initiate MAT than attendings, and most consider it very important to have training in buprenorphine initiation [ 17 , 18 ]. Nonetheless, the role of formal training for EM residents in recognizing, administering, and prescribing buprenorphine has not been established and few programs have developed focused curricula on addiction medicine [ 19 ].…”
Section: Introductionmentioning
confidence: 99%